(untitled) (REVISTA CIENTÍFICA SIGNOS FÓNICOS, 2020)
INTRODUCTION:A protocol is one that is used to name the set of rules, rules and guidelines that serve to guide a behavior or action. The PROHAMET (metalinguistic skills protocol) is an instrument for measuring metalinguistic skills (reading, writing and operational memory) for fourth grade children. METHODS:The research proposal is of a qualitative-quantitative descriptive type since it is in charge of clarifying the relationship between learning with the processes of reading, writing and operational memory in children in primary school. The characteristics of this population indicate that a child in all his capacities is able to execute tasks and activities that demonstrate a good ability in the processes mentioned above. RESULTS:The protocol has a manual, a booklet of answers, and an evaluation grid. The observations made by the experts and the results obtained in the first application that consist of the validation of the pre-designed activities are taken into account. ANALYSIS AND DISCUSSION:the interventionin metalinguistic skills must be integrated into cognitive processes, to enable them to develop properly. For this reason, the role of the speech therapist is very important when implementing protocols that help identify metalinguistic skills in three important sections READING, WRITING AND OPERATING MEMORY, as well as achieving the identification of alterations that may occur in schoolchildren. Elementary school during the learning process. CONCLUSIONS:It is essential for the adequate development of learning the presence of metalinguistic skills, allowing the child an adequate acquisition in the literacy process; The stimulation of metalinguistic skills in the first years of children’s learning causes a representative progress in it, thus favoring highschool performance. It is important to evaluate metalinguistic skills by dividing them into the READING, WRITING AND OPERATING MEMORY sections, allowing an analysis of the skills acquired during learning until the fourth grade of primary education focused on Colombian education.